Data for "Hole-selective SiNx and AlOx tunnel nanolayers for improved polysilicon passivating contacts" - McNab, S; Morriset, A; Libraro, S; Genc, E; Niu, X; Swallow, JEN; Wilshaw, P; Weatherup, RS; Wright, M; Haug, F-J; Bonilla Osorio, RS (University of Oxford, 2024)
Tabulated data set in MS Excel and image files associated with research.